Pengaruh Brand Image, E-Service Quality dan Digital Payment terhadap Customer Satisfaction pada Pengguna Shopeefood di Kota Bandung - Ahmad Abdul Aziz; Dedy Ansari Harahap; Septiana Ayu Esti Maharani (UNISBA Press, 2022)
Abstract. This research focuses on the application of Brand Image, E-Service Quality and Digital Payment to Customer Satisfaction. The purpose of this study was to determine the effect. Brand Image, E-Service Quality and Digital Payment Towards Customer Satisfaction on Shopeefood Users in Bandung. This research is included in the type of quantitative research using a correlation approach. Data collection techniques in this study were carried out through the distribution of questionnaires. The object of this research is Shopeefood users as many as 200 people and narrowed in the number of samples as many as 170 consumers. The sampling technique used in this research is simple random sampling, where the researcher determines the sample randomly. Analysis of the data used is descriptive and statistical analysis by using multiple linear regression analysis, F test and T test. The results of this study indicate that the Brand Image variable partially has a significant effect on Customer Satisfaction, the E-Service Quality variable partially has a significant effect on Customer Satisfaction and the Digital Payment variable partially has a significant effect on Customer Satisfaction. And simultaneously the variables of Brand Image, E-Service Quality and Digital Payment have a significant effect on Customer Satisfaction on Shopeefood Users in Bandung City. Abstrak. Penelitian ini berfokus pada penerapan Brand Image, E-Service Quality dan Digital Payment Terhadap Customer Satisfaction. Tujuan penelitian ini untuk mengetahui pengaruh. Brand Image, E-Service Quality dan Digital Payment Terhadap Customer Satisfaction Pada Pengguna Shopeefood.di Kota Bandung. Penelitian ini termasuk kedalam jenis penelitian kuantitatif dengan menggunakan pendekatan korelasi. Teknik pengumpulan data dalam penelitian ini dilakukan melalui penyebaran angket. Objek penelitian ini adalah pengguna Shopeefood sebanyak 200 orang dan dikerucutkan dalam jumlah sampel sebanyak 170 orang konsumen. Teknik sampling yang digunakan dalam penelitian ini adalah simple random sampling, dimana peneliti menentukan sampel secara acak. Analisis data yang digunakan adalah analisis deksriptif dan statistik yaitu dengan menggunakan analisis regresi linier berganda, uji F dan uji T. Hasil dari penelitian ini menunjukkan bahwa variabel Brand Image secara parsial berpengaruh signifikan terhadap Customer Satisfaction, variabel E-Service Quality secara parsial berpengaruh signifikan terhadap Customer Satisfaction dan variabel Digital Payment secara parsial berpengaruh signifikan terhadap Customer Satisfaction. Dan secara simultan variabel Brand Image, E- Service Quality dan Digital Payment berpengaruh signifikan terhadap Customer Satisfaction pada Pengguna Shopeefood di Kota Bandung.